(untitled) (مجلة إحالات, 2025)
أخذ التأويل في الدرس الغربي مسار تحولات هامة استطاعت أن تشكل مفهومه وحدوده،بدءا من إشكالية فهم النصوص المقدسة وتفسيرها مستعينة بالموروث الاغريقي،لتنطلق كمنحى فعلي مع الفلسفة مع شلايرماخر ودلتاي وتمتد مع ريكور وايكو،ثم استثمار النقد وارتكازه على هذه المرجعية في قراءة النصوص والخطابات،ليرتسم طريق التأويل بين حدود الدين،الفلسفة،النقد. Abstarct: The Esoteric hermeneutics in the Western lesson took a part of important transformations which were able to form its concept and limits, starting from the problem of understanding and interpretation of the holy texts Using the Greek heritage, to start as an actual guide with philosophy by Schleiermacher and Deltay and extend with Ricorer and Eco, then comes the investment of the criticism based on this reference in the reading of texts and speeches, finally, setting up the process of hermeneutics between the limits of religion, philosophy, and criticism